2017
DOI: 10.1016/j.appet.2016.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Fat and lean tissue accretion in relation to reward motivation in children

Abstract: Abstract'Reward sensitivity' explains inter-individual differences in the motivation to obtain rewards when reward cues are perceived. This psychobiological trait has been linked to higher consumption of palatable food when exposed to palatable food cues. The current study aims to examine if reward sensitivity explains differences in patterns of fat and lean tissue accretion over time in children. A longitudinal observational study with measurement waves in 2011 (baseline), 2012, 2013, and 2015 was conducted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…Results are in line with previous longitudinal evidence for a causal influence of personality and psychopathology measures on childhood obesity (Anzman-Frasca et al, 2015; Blaine, 2008; Camfferman et al, 2016; Christensen et al, 2019; De Decker et al, 2017; Derks et al, 2019; Korczak et al, 2013) as well as studies suggesting obesity and eating behavior to have a bidirectional relationship (Antoniou et al, 2016; Herle et al, 2021; Reed et al, 2017). Some studies suggested that childhood obesity may also influence psychopathology (Bradley et al, 2008; Hübel et al, 2019; Korczak et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Results are in line with previous longitudinal evidence for a causal influence of personality and psychopathology measures on childhood obesity (Anzman-Frasca et al, 2015; Blaine, 2008; Camfferman et al, 2016; Christensen et al, 2019; De Decker et al, 2017; Derks et al, 2019; Korczak et al, 2013) as well as studies suggesting obesity and eating behavior to have a bidirectional relationship (Antoniou et al, 2016; Herle et al, 2021; Reed et al, 2017). Some studies suggested that childhood obesity may also influence psychopathology (Bradley et al, 2008; Hübel et al, 2019; Korczak et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…However, few studies have tested these causal assumptions. Longitudinal evidence suggests causal links from inhibitory control (29), reward responsiveness (30), prosociality (31), depression (32, 33), aggression (34), and psychopathology in general (35) to childhood obesity. BMI has additionally been found to influence internalizing problems (36) and depression (33) suggesting a reciprocal relationship between childhood obesity and depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High reward drive has been shown to longitudinally predict problems with various reinforcing substances ( De Decker et al, 2017; Heinrich et al, 2016; Urošević et al, 2015 ) and individuals with internet gaming disorder are significantly higher in reward drive than healthy controls ( Lee et al, 2017; Rho et al, 2017 ). Reward drive peaks during adolescence, presenting a unique period of risk for a range of problematic approach behaviours ( Ernst et al, 2005; Galvan et al, 2006; Gullo & Dawe, 2008; Steinberg & Chein, 2015 ).…”
Section: Some Individuals Are More Sensitive To Rewardmentioning
confidence: 99%
“…Youth with a high sensitivity to reward have been shown to have higher intakes of palatable, energy dense foods and sugar-sweetened beverages (De Decker et al, 2016, De Cock et al, 2016a, De Cock et al, 2016b) and a higher BMI (De Decker et al, 2016). A longitudinal study in a cohort of Flemish children furthermore indicated that girls, but not boys, with heightened reward sensitivity showed significantly higher fat mass levels at baseline and higher fat tissue accretion over a 4-year period (De Decker et al, 2017).…”
Section: Appetitive Traitsmentioning
confidence: 99%